On optimal stopping for the Markov chain with discounting - Mackevičius, V. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Мацкявичюс. Об оптимальной остановке марковской цепи с переоценкойV. Mackevičius. Apie Markovo grandinės su perkainojimu optimalų sustabdymų